Foresight Monitoring Tool Brief - Poulos, Allison; Almanzar, Manuel Ricardo; Wolday, Tsega; Gotor, Elisabetta; Tobon, Hector (Bioversity International and the International Center for Tropical Agriculture, 2023)
The Foresight Monitoring Tool for Adaptive Management and Learning was designed to support planning, reporting, managing, and learning along the Foresight Initiative Theory of Change (ToC) which is populated by a number of knowledge products, capacity sharing activities and innovations generated by the synergistic collaboration of a multidisciplinary team of scientists from 11 CGIAR Centers and external partners. The Foresight Monitoring Tool was reported as an Innovation in 2022. This Brief provides an overview of the 2023 developments which include (1) enhancements to planning along the theory of change; (2) a mechanism to measure value for money; and (3) providing intelligence on scientists' research to understand what they are working on, with whom and where. The brief is illustrated with visuals from the Foresight Monitoring Tool Power BI Dashboard. The brief also summarizes the major challenge and next steps for 2024.